Math
posted by Johnathan .
Prove that:
P(A n B^c) = P(A U B)  P(B)
and
P(A n B^c) = P(A)  P(A n B)
Respond to this Question
Similar Questions

Very easy math
my teacher told me that the inverse of addition was subtraction and that the inverse of subtraction was addition... could you prove it to me x = (1)x ((1)x)^1 I don't see how I'm suppose to get + x by taking the inverse of x i've … 
math
My math teacher wants us to prove that all of our answers are correct. But how am I supposed to be able to prove stuff, like this, for example. The directions want you to write out the words in to an equation. Seven is the sum of X … 
College Math : Linear Algebra
Suppose A is a square matrix satisfying the equation A^3  2I = 0. Prove that A and (A  I) respectively are invertible. (the hint is to find an explicit equation for A^1. To prove A is invertible, this is what I did although I don't … 
math
Let f:A>B, where A and B are nonempty, and let T1 and T2 be subsets of B. a.Prove that f^1(T1 U T2)= f^1(T1) U f^1(T2). b.Prove that f^1(T1 intersects T2) = f^1(T1) intersects f^1(T2). I think once I see a I can do b. c. … 
Math
Prove :cosxcosy= 2sin(x+y/2)sin(xy/2) Prove: 2cot2tanx= 42sec^2x / tanx 
math
Use the Generalized PMI to prove: 2^n > n^2, for all n > 4 First of all, it's true for n=5. Then to prove it for n+1... Assume 2^n > n^2. Then 2^(n+1) = 2*2^n > 2*n^2 > 2*(4n) since n>4 => n^2>4n I'm stuck there. 
math
Given: ; CE=CA ,EB AND AD are medians Prove: EB=AD 2.)Write a paragraph proof. Given: AC bisects <DAB and <DCB . Prove: DAC=BAC? 
Math
I have math HW and these are the questions i wasn't aware of how to answer... please help. a)Prove that 4xy1=0 is parallel to y=4x5 b)Show that the points A(3,1), B(5,2) and C(11,5) are collinear c)Show that the lines y=2x4 and … 
Math Proof
Prove: Let a,b exist in the reals with a<b, (i) For the open interval E=(a,b) prove that the inf E=a and sup E=b (ii) for the closed interval F=[a,b], prove that inf F=a and sup F=b. 
Math
Find inverse of f if f(x)= x^24x+3, (for x is smaller than and equal to 2). First prove that f(x) is one to one in the defined domain of f and then obtain the inverse function. I know how to find the inverse. We just switch x and …